2020
DOI: 10.1002/ajpa.24004
|View full text |Cite
|
Sign up to set email alerts
|

Evolvability in human postcranial traits across ecogeographic regions

Abstract: Objectives: Though recent quantitative genetic analyses have indicated that directional selection appears to be acting on limb lengths and measures of body size in modern humans, these studies assume equal evolvability across modern human groups. However, differences in trait covariance structure due to ancient migration patterns and/or selection may limit the evolvability of populations further from Africa. This study therefore explores patterns of human evolvability across ecogeographic regions. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…The results of the mixed‐effects models both corroborate previous findings as well as contribute information and nuance to understanding the evolution of limb lengths and body size among humans. The latitude and minimum temperature mixed‐effects models indicate that natural selection was responsible for some trait evolution, especially in measures of body size, which further supports studies that have used different evolutionary models to arrive at the same conclusion (Betti et al, 2012; Roseman & Auerbach, 2015; Savell, 2020; Savell et al, 2016). By approaching the evolutionary model with fixed effects of latitude and temperature variables, however, this study demonstrates that these variables may not have contributed as much to selection across body proportion traits as previously suspected, and that we may have underestimated the role of stabilizing selection, population history, neutral evolutionary processes, and covariance in the evolution of these measures.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The results of the mixed‐effects models both corroborate previous findings as well as contribute information and nuance to understanding the evolution of limb lengths and body size among humans. The latitude and minimum temperature mixed‐effects models indicate that natural selection was responsible for some trait evolution, especially in measures of body size, which further supports studies that have used different evolutionary models to arrive at the same conclusion (Betti et al, 2012; Roseman & Auerbach, 2015; Savell, 2020; Savell et al, 2016). By approaching the evolutionary model with fixed effects of latitude and temperature variables, however, this study demonstrates that these variables may not have contributed as much to selection across body proportion traits as previously suspected, and that we may have underestimated the role of stabilizing selection, population history, neutral evolutionary processes, and covariance in the evolution of these measures.…”
Section: Discussionsupporting
confidence: 69%
“…If decades of prior research equating human morphological variation with global patterns of climate are supported, we expect to find evidence that climatic variables and latitude both present the best models to explain variation in limb length and measures of body mass, and that this variation is best explained by models representing response to directional natural selection. Previous studies (Savell, 2020; Savell et al, 2016) demonstrated that long bone lengths form a distinct integrated set from dimensions associated with body size and breadth, and so we also expect these two integrated groups to exhibit independent relationships with both responses to selection in climate or latitude as well as population structure.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…This assumes that the estimated P or G from the extant population is similar enough to G in the ancestral, extinct population. Based on similarities between closely related extant species, a wide array of work (both neontological and paleontological) has assumed that P (or G ) from an extant population is representative of the ancestral G , which has allowed researchers to make evolutionary inferences from phenotypic data across macroevolutionary timescales in ways that would otherwise be impossible (Ackermann and Cheverud 2004; de Oliveira et al 2009; Rolian 2009; Marroig and Cheverud 2010; Young et al 2010; Grabowski et al 2011; Grabowski 2013; Baab 2018; Villamil 2018; Savell 2020; Agosto and Auerbach 2021).…”
Section: Quantitative Genetics In the Rock Recordmentioning
confidence: 99%